H1N1 vaccines in a large observational cohort of patients with inflammatory bowel disease treated with immunomodulators and biological therapy. Issue 4 (26th January 2011) - Rahier, Jean-François; Papay, Pavol; Salleron, Julia; Sebastian, Shaji; Marzo, Manuela; Peyrin-Biroulet, Laurent; Garcia-Sanchez, Valle; Fries, Walter; van Asseldonk, Dirk P; Farkas, Klaudia; de Boer, Nanne K; Sipponen, Taina; et al.
Abstract : Background: Safety data are lacking on influenza vaccination in general and on A (H1N1)v vaccination in particular in patients with inflammatory bowel disease (IBD) receiving immmunomodulators and/or biological therapy. Aims and methods: The authors conducted a multicentre observational cohort study to evaluate symptoms associated with influenza H1N1 adjuvanted (Pandemrix, Focetria, FluvalP) and non-adjuvanted (Celvapan) vaccines and to assess the risk of flare of IBD after vaccination. Patients with stable IBD treated with immunomodulators and/or biological therapy were recruited from November 2009 until March 2010 in 12 European countries. Harvey–Bradshaw Index and Partial Mayo Score were used to assess disease activity before and 4 weeks after vaccination in Crohn's disease (CD) and ulcerative colitis (UC). Vaccination-related events up to 7 days after vaccination were recorded. Results: Of 575 patients enrolled (407 CD, 159 UC and nine indeterminate colitis; 53.9% female; mean age 40.3 years, SD 13.9), local and systemic symptoms were reported by 34.6% and 15.5% of patients, respectively. The most common local and systemic reactions were pain in 32.8% and fatigue in 6.1% of subjects. Local symptoms were more common with adjuvanted (39.3%) than non-adjuvanted (3.9%) vaccines (p<0.0001), whereas rates of systemic symptoms were similar with both types (15.0% vs 18.4%, p=0.44). Among the adjuvanted group, Pandemrix more often induced local reactions than FluvalP and Focetria (51.2% vs 27.6% and 15.4%, p<0.0001). Solicited adverse events were not associated with any patient characteristics, specific immunomodulatory treatment, or biological therapy. Four weeks after vaccination, absence of flare was observed in 377 patients with CD (96.7%) and 151 with UC (95.6%). Conclusion: Influenza A (H1N1)v vaccines are well tolerated in patients with IBD. Non-adjuvanted vaccines are associated with fewer local reactions. The risk of IBD flare is probably not increased after H1N1 vaccination.